Respostas
respondido por:
2
(x+3)(1-x)/(x-2) > 0
p=(x+3)(1-x)=x-x²+3-3x =-x²-2x+3 ...a=-1<0
raízes x=-3 e x=1
p-----------------(-3)++++++++(1)-----------------
######Se a>0 seria ++++(-3)------(1)++++++++
q=x-2 ...raiz x=2 ...a=1>0q------------------(2)++++++++++++++
######Se a<0 seria ++++++++(2)----------------
Estudo de sinais:
p----------(-3)++++++++(1)-----------------
q-------------------------------------(2)+++++
p/q++++(-3)--------------(1)+++(2)--------
(-∞,-3) U (1,2) é a resposta
p=(x+3)(1-x)=x-x²+3-3x =-x²-2x+3 ...a=-1<0
raízes x=-3 e x=1
p-----------------(-3)++++++++(1)-----------------
######Se a>0 seria ++++(-3)------(1)++++++++
q=x-2 ...raiz x=2 ...a=1>0q------------------(2)++++++++++++++
######Se a<0 seria ++++++++(2)----------------
Estudo de sinais:
p----------(-3)++++++++(1)-----------------
q-------------------------------------(2)+++++
p/q++++(-3)--------------(1)+++(2)--------
(-∞,-3) U (1,2) é a resposta
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás